Acquisitive Liberations: A Critical Evaluation of the Use of Human Rights Discourse in Justifying Military Intervention - Williams, Martin Paul George (Kent Law Review, 2018)
Military intervention into the affairs of other states is often justified by the United States of America with reference to human rights, and is therefore called humanitarian intervention. This article examines the operation of the human rights discourse in justifying such intervention, and argues that the conflation of national self-interest and collective self-defence, which is allowed for in jus ad bellum discourse and built into the UN legal and executive architecture, allows for intervening states to present military actions that afford them strategic gain and commercial opportunity as altruistic acts. Support, weak resistance or acquiescence to such action by the UN and by the press allows for such actions to acquire popular legitimacy, and this article examines how the human rights discourse provides an argumentative framework to articulate such legitimacy. In its critical analysis of arguments put forward by Simma and Cassese, the article concludes that the conduct of intervening states post bellum should attract as much legal scrutiny as the initial intervention, and that the use of human rights to justify interventions that are acquisitive in motive undermines the purpose and operations of human rights as a driver for positive change in the world.